Enhancing protein to extremely high content in photosynthetic bacteria during biogas slurry treatment. (December 2017) - Yang, Anqi; Zhang, Guangming; Meng, Fan; Lu, Pei; Wang, Xintian; Peng, Meng
Graphical abstract: Highlights: Protein content of PSB reached 90% during biogas slurry treatment. High salinity and high ammonia were the main causes for protein enhancement. Biogas slurry provided a buffer system for PSB to resist the stresses. Glutamate synthase and glutamine synthetase activities were enhanced. Abstract: This work proposed a novel approach to achieve an extremely high protein content in photosynthetic bacteria (PSB) using biogas slurry as a culturing medium. The results showed the protein content of PSB could be enhanced strongly to 90% in the biogas slurry, which was much higher than reported microbial protein contents. The slurry was partially purified at the same time. Dark-aerobic was more beneficial than light-anaerobic condition for protein accumulation. High salinity and high ammonia of the biogas slurry were the main causes for protein enhancement. In addition, the biogas slurry provided a good buffer system for PSB to grow. The biosynthesis mechanism of protein in PSB was explored according to theoretical analysis. During biogas slurry treatment, the activities of glutamate synthase and glutamine synthetase were increased by 26.55%, 46.95% respectively.